Love and care practices in sustaining brotherhood and unity - Mhd Sarif, Suhaimi; Ismail, Yusof; Abdul Wahid, Mohamad Fikri (Kulliyyah of Economics and Management Sciences IIUM, 2022)
Brotherhood and unity are interrelated. Brotherhood contributes to unity. How about the contributing factor to brotherhood? In any bonding, there must be a connection between the hearts of the individuals. Love and care tie the bonding. This chapter describes the love and care practices in sustaining brotherhood and unity in the contexts of Muslims in Australia. The aim of the chapter is to explore the influence of love and care practices in sustaining brotherhood and unity. The study uses qualitative case study method to obtain the insights and views about the love and care practices. The results of the study showed that frequency of connections and gatherings contribute to brotherhood and unity.